2014
DOI: 10.1017/erm.2014.9
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived stromal cells for osteoarticular repair: trophic function versus stem cell activity

Abstract: The identification of multipotent adipose-derived stromal cells (ASC) has raised hope that tissue regeneration approaches established with bone-marrow-derived stromal cells (BMSC) can be reproduced with a cell-type that is far more accessible in large quantities. Recent detailed comparisons, however, revealed subtle functional differences between ASC and BMSC, stressing the concept of a common mesenchymal progenitor existing in a perivascular niche across all tissues. Focussing on bone and cartilage repair, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 155 publications
(272 reference statements)
3
48
0
Order By: Relevance
“…Stem cell therapy is in its infancy and we are only gradually understanding how best to use these cells in the clinical setting. While much research effort has concentrated on understanding how we can effectively differentiate MSCs to specific committed lineages [23,[31][32][33][34][35][36][37][38][39][40][41], there has been growing interest in the trophic effects of the undifferentiated cells mediated through secretion of growth factors [13][14][15][16][17]. Based on our original in vitro observations [12] we hypothesized that combining undifferentiated MSCs with a collagen scaffold, we could deliver the cells directly into the site of injury and maximize the chance of secreted trophic factors driving a tissue repair response.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell therapy is in its infancy and we are only gradually understanding how best to use these cells in the clinical setting. While much research effort has concentrated on understanding how we can effectively differentiate MSCs to specific committed lineages [23,[31][32][33][34][35][36][37][38][39][40][41], there has been growing interest in the trophic effects of the undifferentiated cells mediated through secretion of growth factors [13][14][15][16][17]. Based on our original in vitro observations [12] we hypothesized that combining undifferentiated MSCs with a collagen scaffold, we could deliver the cells directly into the site of injury and maximize the chance of secreted trophic factors driving a tissue repair response.…”
Section: Discussionmentioning
confidence: 99%
“…However, a statistically significant increase in bone was not found in ASC‐treated allografts suggesting ASC delivery alone or with co‐delivered FGF‐2 and TGF‐β1 was insufficient for robust new bone formation. It has been previously reported that ASCs may have less of an osteogenic potential than similar mesenchymal stem cells derived from bone marrow cells and require osteogenic pre‐induction before implantation for robust bone formation . The ASCs used in this experiment were not osteogenically induced prior to implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Current treatments of osteochondral defects by reconstructive plastic and orthopaedic surgery procedures are unable to restore the function of damaged tissues; they are only palliative and not curative (Orth et al , ). Tissue engineering has been proposed as an alternative strategy to repair osteochondral defects (Ruetze and Richter, ; Veronesi et al , ) and a potential alternative to regenerate bone, cartilage and the bone–cartilage interface (Nukavarapu and Dorcemus, ). New strategies of tissue engineering strongly support the simultaneous use of scaffolds, cells and growth factors (Hosseinkhani et al ., ).…”
Section: Introductionmentioning
confidence: 99%